Multi-generational impacts of organic contaminated stream water on Daphnia magna: A combined proteomics, epigenetics and ecotoxicity approach. (June 2019) - Chatterjee, Nivedita; Choi, Suhyon; Kwon, Oh Kwang; Lee, Sangkyu; Choi, Jinhee
Abstract: The present study aimed to elucidate the mechanisms of organismal sensitivity and/or physiological adaptation in the contaminated water environment. Multigenerational cultures (F0, F1, F2) of Daphnia magna in collected stream water (OCSW), contaminated with high fecal coliform, altered the reproductive scenario (changes in first brood size timing, clutch numbers, clutch size etc.), compromised fitness (increase hemoglobin, alteration in behavior), and affected global DNA methylation (hypermethylation) without affecting survival. Using proteomics approach, we found 288 proteins in F0 and 139 proteins in F2 that were significantly differentially upregulated after OCSW exposure. The individual protein expressions, biological processes and molecular functions were mainly related to metabolic processes, development and reproduction, transport (protein/lipid/oxygen), antioxidant activity, increased globin and S-adenosylmethionine synthase protein level etc., which was further found to be connected to phenotype-dependent endpoints. The proteomics pathway analysis evoked proteasome, chaperone family proteins, neuronal disease pathways (such as, Parkinson's disease) and apoptosis signaling pathways in OCSW-F0, which might be the cause of behavioral and developmental alterations in OCSW-F0. Finally, chronic multigenerational exposure to OCSW exhibited slow physiological adaptation in most of the measured effects, including proteomics analysis, from the F0 to F2 generations. The common upregulated proteins in both generations (F0 & F2), such as, globin, vitellinogen, lipid transport proteins etc., were possibly play the pivotal role in the organism's physiological adaptation. Taken together, our results, obtained with a multilevel approach, provide new insight of the molecular mechanism in fecal coliform-induced phenotypic plasticity in Daphnia magna . Graphical abstract: Image 1 Highlights: Multigenerational exposure of Daphnia magna to organic contaminated stream water. Altered reproduction, physiology, behavior, DNA methylation without affecting survival. Proteomics & bioinformatics analysis supports phenotype-dependent endpoints. Sensitivity (F0) to physiological adaptation (F2): fecal coliform-induced phenotypic plasticity. Involvement of globin, vitellinogen, lipid transport proteins in physiological adaptation. Abstract : CapsuleStress to physiological adaptation in organic contaminated stream water exposed Daphnia magna .